The Effect of Service Quality, Price and Promotion on Purchase Decisions on Yuuk Mie SMEs in Sidoarjo Regency - Nur Hayati Eka Kusniawati; Misti Hariasih (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to determine the effect of service quality, price and promotion on purchasing decisions on Yuk Mie SMEs in Keboharan Village, Sidoarjo. This research is a descriptive study using quantitative methods. The population used in this study were all consumers who had bought Yuk Mie UMKM products in Keboharan Village. Data collection techniques using a questionnaire with a total of 96 respondents. The sampling technique used was non-probability sampling with the Accidental Sampling method. The data analysis technique used in this study is multiple linear regression using the SPSS version 25 program. The results show that service quality has a significant and positive effect on purchasing decisions, price has a significant and positive effect on purchasing decisions, promotions have a significant and positive effect on purchasing decisions. and the influence of service quality, price and promotion have a joint effect on purchasing decisions. Keywords: Service Quality, Price, Promotion, Purchase Decision